Sunan Ampel Dan Dakwahnya Dalam Islamisasi Jawa Timur - Raihan Syach Bustami Harahap; Tenny Sudjatnika; Andini Marizka Siregar (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2023)
The expansion of Islam in Indonesia started in the middle of the 7th century AD. The expansion of Islam cannot be separated from the role of Walisongo as the guardian and assembly of Sufism experts in Indonesia, especially in Java. Sunan Ampel became one of the figures who made a major contribution to spreading Islam in East Java. The aim of this research is to find out the background of Sunan Ampel to Java and how Sunan Ampel spread Islam with his preaching in East Java. This research aims to understand the strategies used by Sunan Ampel while spreading Islam in East Java. This research uses a historical research method with a qualitative research model. The main sources used in carrying out this research are several books, journals, and babad that are relevant to the research topic studied. The results and discussion of this research concluded that Sunan Ampel's da'wah strategy through marriage, relatives, and building mosques and Islamic boarding schools, as well as teaching Islamic knowledge to the surrounding community seemed still not practical and was still considered difficult to accept by the surrounding community at that time. Keywords: Sunan Ampel; Preaching; Surabaya; East Java.